Sending the Signal to Bone: How Tumor-Derived EVs Orchestrate Pre-Metastatic Niche Formation and Skeletal Colonization - Alhomam Dabaliz; Hagar Mahmoud; Raffi AlMutawa; Khalid S. Mohammad (Biomedicines, 2025)
Bone is a preferred site for disseminated tumor cells, yet the molecular mechanisms that prepare the skeletal microenvironment for metastatic colonization are only beginning to be understood. At the heart of this process are extracellular vesicles (EVs), nano-sized, lipid-encapsulated particles secreted by cancer cells and stromal components. This review consolidates current findings that position EVs as key architects of the bone-metastatic niche. We detail the biogenesis of EVs and their organotropic distribution, focusing on how integrin patterns and bone-specific ligands guide vesicle homing to mineralized tissues. We then outline the sequential establishment of the pre-metastatic niche, driven by EV-mediated processes including fibronectin deposition, stromal cell reprogramming, angiogenesis, neurogenesis, metabolic reconfiguration, and immune modulation, specifically, the expansion of myeloid-derived suppressor cells and impaired lymphocyte function. Within the bone microenvironment, tumor-derived EVs carrying microRNAs and proteins shift the balance toward osteoclastogenesis, inhibit osteoblast differentiation, and disrupt osteocyte signaling. These alterations promote osteolytic destruction or aberrant bone formation depending on tumor type. We also highlight cutting-edge imaging modalities and single-EV omics technologies that resolve EV heterogeneity and identify potential biomarkers detectable in plasma and urine. Finally, we explore therapeutic approaches targeting EVs, such as inhibition of nSMase2 or Rab27A, extracorporeal EV clearance, and delivery of engineered, bone-targeted vesicles, while addressing translational challenges and regulatory considerations. This review offers a roadmap for leveraging EV biology in predicting, preventing, and treating skeletal metastases by integrating advances across basic biology, bioengineering, and translational science.